2015
DOI: 10.1002/stem.2085
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Naïve Human Pluripotency

Abstract: Naïve or ground state pluripotency is a cellular state in vitro which resembles cells of the preimplantation epiblast in vivo. This state was first observed in mouse embryonic stem cells and is characterized by high rates of proliferation, the ability to differentiate widely, and global hypomethylation. Human pluripotent stem cells (hPSCs) correspond to a later or “primed” stage of embryonic development. The conversion of hPSCs to a naïve state is desirable as their features should facilitate techniques such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 48 publications
(176 reference statements)
0
24
0
1
Order By: Relevance
“…It is clear that naïve cells are more robust than primed cells, both in their growth rate and in their ability to contribute to the differentiated cell population in injected blastocycts (Brons et al, 2007; Dodsworth et al, 2015; Silva et al, 2008; Tesar et al, 2007). Indeed, we found that knocking out SirT1 also slowed the growth of naïve cells and by some assays altered their morphology to resemble primed cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that naïve cells are more robust than primed cells, both in their growth rate and in their ability to contribute to the differentiated cell population in injected blastocycts (Brons et al, 2007; Dodsworth et al, 2015; Silva et al, 2008; Tesar et al, 2007). Indeed, we found that knocking out SirT1 also slowed the growth of naïve cells and by some assays altered their morphology to resemble primed cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to stably reprogram human embryonic stem cells to the naïve state using both genetic (Takashima et al, 2014; Wang et al, 2011) and chemical methodologies (Chan et al, 2013; Duggal et al, 2015; Gafni et al, 2013; Hanna et al, 2010; Theunissen et al, 2014; Valamehr et al, 2014; Ware et al, 2014). These studies have been met with varying levels of success, but the robustness of these protocols with regards to the long term culture of the naïve state is still being evaluated (Dodsworth et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that the Momiji mouse strain will provide a powerful tool for tracing the reprogramming involved in establishing iPSCs (EpiSCs→iPSCs) and will help to clarify how XCR participates in this process. Clarification of the reprogramming processes, from a primed to a naïve state, will help in the effective establishment of naïve human iPSCs from primed ESCs (Dodsworth et al, 2015;Pera, 2014). …”
Section: Advantages and Future Research Perspectives For Momiji Micementioning
confidence: 99%
“…RTKs play pivotal roles in cell‐fate control of many cell types. For instance, basic fibroblast growth factor (bFGF) is essential for maintaining human embryonic stem cells, whereas vascular endothelial growth factor (VEGF) induces differentiation into endothelial cells . In neural stem cells, epidermal growth factor (EGF) and bFGF are required for self‐renewal, whereas nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF) trigger differentiation into neurons .…”
Section: Discussionmentioning
confidence: 99%